Supporting schools in their journey to inclusive education: review of guides and tools. Issue 1 (1st February 2021) - Sandoval, Marta; Muñoz, Yolanda; Márquez, Carmen
Abstract : This study presents a review of the guides and tools found in the literature regarding the implementation of inclusive education to support schools in the development and improvement of their educational practices. A total of 22 guides were reviewed, with their corresponding analyses of: the purpose for which they were created, their inclusive perspective, their target social group, the stage at which they are most efficient, the action strategies they propose, the basic structure on which they are founded, the dimensions and indicators on which they stimulate reflection and the evaluation tools and instruments they propose. The conclusions highlight the need to use and show the content of this type of resources, generating spaces for reflection in school communities.